Exercise and obesity management: Bibliometrics Analysis / Muhammad Adham Izudin - Izudin, Muhammad Adham (2022)
The main objective of this thesis work is to assess and map international research concerning gender in science and higher education. To do this, two different studies were designed: first, to examine the development and growth of scientific literature on exercise and obesity management, and, second, to map and analyse the structure and evolution of the scientific literature on exercise and obesity management, focusing on factors related to differences. For the development and growth of scientific literature on exercise and obesity management, a total corpus of 4195 and 4722 articles published between 1996 and 2020 for WoS while for Scopus between 1930 and 2020, were extracted from the Thomson Reuters Web of Science and Scopus database, respectively. Subsequently, this research mapped the evolution of scientific literature on exercise and obesity management consisting of co-occurrence and relationship between major keywords used in searched corpus. The methodology and procedures employed included standard bibliometric indicators. Various bibliometric parameters are extracted, such as: total papers, total citations, and citation per paper. Top 10 of the most productive and highly cited authors, major subject areas, sources or journals, countries, and institutions are also evaluated. Further, a list of highly influential papers is also assessed. The results of these studies suggest an upward trend in both the number of papers (n = 4195 for WoS) and (n = 4722 for Scopus), and also the number of authors per paper (n = 21 for WoS) also (n = 159 for Scopus). Interest in exercise and obesity management extends to many journals (n = 25 for Wos) and (n = 160 for scopus), countries (n = 25) and institutions (n = 21 for WoS and Scopus). The data showed a small dispersion of research influence, with a small number of researchers gaining major citation impact. In summary, this research portrays the growth structure of exercise and obesity management during 1996 and 2020 for WoS while for Scopus between 1930 and 2020, and provides the concise background overview of exercise and obesity management related works with various relationships to other relevant themes.